ANALISIS SYAIR “ HATI PEREMPUAN ADALAH BATU-BATU “ KARYA ABBAS BIN AHNAF : KAJIAN ILMU MA’ANI - mutmainnah, mutmainnah; Wahyuni, Sri (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2024)
This research is related to the analysis of a poem entitled "Women's Hearts are Stones" by Abbas bin Ahnaf, by analyzing the uslub kalam insha'i in it according to a review of ma'ani science. The aim of this research is to find out poetry in general during the Abbasid Dynasty, including its definition, position and purpose. As well as specifically discussing Abbas bin Ahnaf and his love poems. This research also aims to analyze uslub kalam insha'i in one of Abbas bin Ahnaf's poems entitled "Women's hearts are stones". In this research, the researcher used a qualitative descriptive approach, and used a literature review in collecting data, which required the researcher to read, study in more depth, write and translate literature related to this research to collect data. and using inductive, comparative and historical methods to compile data. So the results of this research are: 1) poetry during the Abbasid Dynasty experienced several changes from previous poetry in terms of type and purpose, meaning and imagination, lafadz and arrangement and rhythm. 2) Abbas bin Ahnaf was the only poet of the Abbasid Dynasty who only focused on writing love poetry. 3) In the seven stanzas of the poem "A woman's heart is a stone", the researcher found several insha' kalam which include Amar, Istifham, Tamanni and Nida'. Amar is found in the second stanza with the meaning ihmal, Istifham is found in the fourth and fifth stanzas, both of which have the same meaning tamanni, Nida' is found in the fourth stanza with the use of the non-original letter nida' and Tamanni is found in the second and fourth stanzas with the use of the tamanni tool. which is also not original.Keywords: Poetry Analysis, Abbas bin Ahnaf, Ma'ani Science